Republic of South Sudan : Technical Assistance Report-Report on External Sector Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2020)
This Technical Assistance Mission has been undertaken to support the Bank of South Sudan (BSS) in improving external sector statistics (ESS). The recommendations made during the 2018 mission for the recording of oil exports and transactions with Sudan under the Transitional Financial Agreement were implemented by the BSS. The mission worked toward enhancing the inter-agency cooperation by meeting with selected public sector bodies, providing them with an overview of the balance of payments and the data that the BSS will request from them. Before the end of the mission, requested data from one of the entities, the Civil Aviation Authority was provided. A work program was developed to conduct a visitor expenditure survey and a preliminary International Reserves and Foreign Currency Liquidity template was submitted to IMF's Statistics Department for review. In order to support progress in the various work areas, the mission recommended a detailed one-year action plan, with the several priority recommendations carrying weight to make headway in improving ESS reliability.